1985
DOI: 10.1002/1097-0142(19850101)55:1<18::aid-cncr2820550104>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Acute promyelocytic leukemia in 57 previously untreated patients

Abstract: Fifty‐seven patients in initial phase of acute promyelocytic leukemia (APL) were treated in the same department with heparin infusion, platelet transfusions, and two related induction regimens both including cytosine arabinoside and daunorubicin. Clinical and biological findings at presentation were studied. The complete remission (CR) rate was 53%. Twenty‐seven patients (47%) died during the initial course of the disease, either before day 5 (early death [ED], n = 7) or after day 5 (death in aplasia [DA], n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
2
2

Year Published

1987
1987
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 41 publications
(1 reference statement)
2
53
2
2
Order By: Relevance
“…This study shows the differentiating capacity of ATRA as an inductor of CR, with 83.7% of the newly diagnosed patients achieving CR during the course of treatment. Such remission rates are similar to those obtained in several other randomized trails with ATRA (4,10) and also to the historical results obtained with standard chemotherapy (11).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study shows the differentiating capacity of ATRA as an inductor of CR, with 83.7% of the newly diagnosed patients achieving CR during the course of treatment. Such remission rates are similar to those obtained in several other randomized trails with ATRA (4,10) and also to the historical results obtained with standard chemotherapy (11).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the leukemic blasts can infiltrate the arteriolar endothelial walls and cause a secondary hemorrhage (15). Therefore, a major concern about APL patients treated with ATRA is early death secondary to hyperleukocytosis during induction treatment (11,16), especially due to RAS and intracerebral hemorrhage. In our study, 4 of 37 patients (11%) had an early death due to intracerebral hemorrhage, with a higher median WBC than in the group that did not develop this lethal complication (48 x 10 3 /mm 3 versus 22.5 x 10 3 /mm 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…20,23,[39][40][41][42][43] In contrast to the improvement in survival and decrease of hemorrhagic complications resulting from the introduction of ATRA, changes in hemorrhagic mortality have been reported to be minimal. 10 In our study, FICH was not decreased after ATRA use (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…3,11,12 The major reason for the bleeding tendency is the disease-and treatment-related thrombocytopenia. Hypofibrinogenemia is a well known and threatening complication of APL.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] It was a frequent cause of serious bleeding before introduction of treatment with all-trans retinoic acid (ATRA). A coagulation disorder similar to that in APL may also occur in other FAB types of AML, but only a few data are available on the incidence in various FAB types, the risk of bleeding and the prognosis of these patients.…”
Section: Introductionmentioning
confidence: 99%